FEATURES OF TEACHERS' READINESS TO ACTIVITIES IN MODERN PRESCHOOL EDUCATIONAL INSTITUTION (Pedagogy of Higher and Secondary Education, 2007)
The article covers of the contemporary the issues of the professional activities the tutors in the pre-school establishment. The analysis the program is on the pre-school education show oneself importance to be ready of the upbringing of responsibility of the person under-fives.